New Anthraquinone‐Based Conjugated Microporous Polymer Cathode with Ultrahigh Specific Surface Area for High‐Performance Lithium‐Ion Batteries. (13th November 2019) - Molina, Antonio; Patil, Nagaraj; Ventosa, Edgar; Liras, Marta; Palma, Jesús; Marcilla, Rebeca
Abstract: Redox‐active conjugated microporous polymers (RCMPs) polymerized by conventional methods are commonly obtained as irregular insoluble solid particles making the electrode processing difficult. In this work, the synthesis of RCMP based on anthraquinone moieties (IEP‐11) is developed via a two‐step pathway combining miniemulsion and solvothermal techniques that results in polymer nanostructures that are much easier to disperse in solvents facilitating the fabrication of electrodes. Interestingly, this synthetic approach is also found to have an important impact on the inherent morphology of IEP‐11 that exhibits a dual porosity combining micro and mesopores with a specific surface area as high as 2200 m 2 g −1, which is one of the highest values reported for RCMPs. Moreover, the compactness of the electrodes is also improved, the resulting electrodes have triple the density than those obtained with conventional methods. Consequently, when these electrodes are tested as cathodes in Li‐ion battery, they deliver high gravimetric capacities (≈100 mAh g −1 ) and extraordinary rate capability keeping 76% of discharge capacity when charged–discharged in only 12 min (@5 C). Moreover, the insoluble and robust conjugated porous structure provides IEP‐11‐E12 with an unprecedented cycling stability retain ≈90% and ≈60% of its initial capacity after 5000 (@2 C) and 80 000 cycles (@30 C), respectively. Abstract : The combined miniemulsion polymerization–solvothermal method yields anthraquinone‐based conjugated microporous polymer nanostructures (IEP‐11‐E12) that are easy to disperse, enabling the fabrication of high‐quality electrodes. Moreover, IEP‐11‐E12 exhibits ultra‐high specific surface area (>2000 m 2 g −1 ) with dual micro‐mesoporosity contributing to their excellent electrochemical performance. Specifically, the assembled Li/IEP‐11‐E12 cell demonstrates improved active‐material utilization, excellent rate capability, and ultralong‐term cyclability.